Does metergoline selectively attenuate 5-HT mediated prolactin release? - Ellis, P; Gartside, SE; Ware, C; Campling, G; Cowen, P (1991)
Administration of the non-selective 5-HT receptor antagonist metergoline (0.5 mg/kg) to male rats attenuated the prolactin response to the 5-HT releasing agent d-fenfluramine (7.5 mg/kg) but not to the dopamine receptor antagonist haloperidol (1.5 mg/kg). In contrast, in healthy male volunteers, pretreatment with metergoline (4 mg orally) abolished the prolactin response to intravenous haloperidol (5 micrograms/kg). The findings suggest that in humans blockade of a prolactin response by a conventional oral dose of metergoline cannot be taken as evidence of involvement of 5-HT-mediated mechanisms.